(untitled) (Foro de Educacion, 2021)
A line of research within the sociology of education focuses on the crucial moment when families choose school for their children. This interest responds, mainly, to the expectations that upper class families have of the school as a space for academic and moral education and networking. Consequently, they understand that the schooling of their children is a fundamental strategy to sustain or improve their position in the social space. In a first quantitative stage, we use the multidimensional construction of the social space of Córdoba, which we carried out with the research team, and in a second qualitative stage we analyzed 36 in-depth interviews for this research. In parallel, the information available on the websites of the schools, contributes to reconstruct the current state of the educational offer for the sample. The recent diversification of the educational offer in Córdoba expose families to face a complexity unthinkable for previous generations. A multiplicity of practices, associated with the process of choosing among the possible schools for their children, seek to optimize the benefit of schooling, adapting the choice to the possibilities. On the other hand, school authorities also select the families. Although the choice of school is presented in the discourse of families as an increasingly rational and democratic moment at the family level, we can see that it is strongly conditioned by determinants associated with their position and trajectory in the social space.